A multi-component parallel-plate flow chamber system for studying the effect of exercise-induced wall shear stress on endothelial cells. Issue 2 (December 2016) - Wang, Yan-Xia; Xiang, Cheng; Liu, Bo; Zhu, Yong; Luan, Yong; Liu, Shu-Tian; Qin, Kai-Rong
Abstract Background In vivo studies have demonstrated that reasonable exercise training can improve endothelial function. To confirm the key role of wall shear stress induced by exercise on endothelial cells, and to understand how wall shear stress affects the structure and the function of endothelial cells, it is crucial to design and fabricate an in vitro multi-component parallel-plate flow chamber system which can closely replicate exercise-induced wall shear stress waveforms in artery. Methods The in vivo wall shear stress waveforms from the common carotid artery of a healthy volunteer in resting and immediately after 30 min acute aerobic cycling exercise were first calculated by measuring the inner diameter and the center-line blood flow velocity with a color Doppler ultrasound. According to the above in vivo wall shear stress waveforms, we designed and fabricated a parallel-plate flow chamber system with appropriate components based on a lumped parameter hemodynamics model. To validate the feasibility of this system, human umbilical vein endothelial cells (HUVECs) line were cultured within the parallel-plate flow chamber under abovementioned two types of wall shear stress waveforms and the intracellular actin microfilaments and nitric oxide (NO) production level were evaluated using fluorescence microscope. Results Our results show that the trends of resting and exercise-induced wall shear stress waveforms, especially the maximal, minimal and mean wall shear stress as well as oscillatory shear index, generated by the parallel-plate flow chamber system are similar to those acquired from the common carotid artery. In addition, the cellular experiments demonstrate that the actin microfilaments and the production of NO within cells exposed to the two different wall shear stress waveforms exhibit different dynamic behaviors; there are larger numbers of actin microfilaments and higher level NO in cells exposed in exercise-induced wall shear stress condition than resting wall shear stress condition. Conclusion The parallel-plate flow chamber system can well reproduce wall shear stress waveforms acquired from the common carotid artery in resting and immediately after exercise states. Furthermore, it can be used for studying the endothelial cells responses under resting and exercise-induced wall shear stress environments in vitro.